Types of Stress and Transitions and Adolescent Self Image - Tolan, Patrick ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Although research has suggested that level of social stress relates to psychosocial problems in adolescents and that social stressors impact more on females than on males, past studies have not considered whether gender differences in stress are related to perception of stressfulness or higher levels of experience, and if any types of events consistently distinguish gender differences. In this study the Offer Self Image Questionnaire (OSIQ) was administered to 84 16- to 18-year-old males and females to test the relationship of ratings and experience of four types of social stressors (Developmental Transitions, Induced Transitions, Daily Hassles, and Circumscribed Events) to self-image. Differences found in the stressfulness ratings of the four stressors were relatively parallel for both genders, and no significant correlations between ratings and experiences were found. Only the Daily Hassles score correlated with the self-image scales for both genders. Comparisons of subjects with clinical range scores and those with normal range scores on the OSIQ indicated that for both genders, the two groups differed significantly only on the Daily Hassles score. The results suggest that gender differences are less influential than previously reported and that day-to-day stress is most influential in overall adjustment. A 23-item reference list and 3 tables are included. (KS)
ERIC Note: Paper presented at the Annual Convention of the American Psychological Association (94th, Washington, DC, August 22-26, 1986). For related document, see CG 019 908.
Educational level discussed: High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Daily Living Skills; Emotional Adjustment; High Schools; Self Concept; Sex Differences; Social Influences; Stress Variables; Reports, Research; Speeches/Meeting Papers